Takwa: Landasan Spiritual dalam Menghadapi Ketimpangan Ekonomi dan Mewujudkan Keadilan Sosial - Dedi Susanto; Achmad Abubakar; Muhammad Galib (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This research examines the role of piety in promoting social justice, with a particular focus on the growing economic inequality in society. Piety, defined as moral and spiritual awareness of responsibility to God, is expected to motivate individuals and communities to act justly and contribute to the improvement of social welfare. Using a descriptive qualitative approach, this study integrates the concept of piety with the theory of social justice proposed by John Rawls, which emphasizes the importance of fair and equitable distribution of resources. The results show that piety has great potential as a driver of inclusive and equitable social policies, encouraging individuals to care more about others. However, challenges in its implementation, including ambiguity in understanding and misuse of piety values to justify injustice, remain to be overcome for piety to truly become a tool for change. The findings are expected to make a significant contribution to the development of more just and equitable public policies, and inspire concrete actions in a more prosperous society.